Oxidative fluorination of iridium metal for urban mining: Kinetic studies; Resource-Efficient Technologies; Vol. 2, Iss. 2 - Sakhnevich B. V. Bogdan; Malin A. V. Artem Vladimirovich; Shagalov V. V. Vladimir Vladimirovich; Sobolev V. I. Vasily Igorevich; Ostvald R. V. Roman Vyacheslavovich; Ivlev S. I. Sergey Ivanovich (2016, 2016)
Title screen